Nano- and micromechanics of polymers : structure modification and improvement of properties - Michler, Goerg H. (Hanser, 2012)
The book brings together the detailed knowledge of structure and morphology of the main classes of polymers, including commodities as well as special polymers, with the explanation of the mechanical properties, processes and mechanisms on macroscopic, microscopic and nanoscopic scale. Description, explanation and theoretical interpretation of all of the micro- and nanoscopic processes and mechanisms in different polymers constitute the central part the book. Thus, it offers a key for a better understanding of structure-property-correlations of nearly all polymers of interest in industrial applications. A central aim of the book is to show, how by changing the morphology, microprocesses and, finally, the mechanical properties can be improved. There is no other book available on the market, which is focused on micromechanical processes of polymers and their role to improve the properties of polymeric materials.